Decision Maker’s Guides for Solid Waste Management Technologies - Kaza, Silpa; Bhada-Tata, Perinaz (World Bank, Washington, DC, 2019)
The Decision Maker’s Guides for Solid Waste Management Technologies were created to help mayors and decision makers understand the various technologies and when they would be appropriate based on local circumstances. Mayors are often approached by different solid waste management technology vendors and these guides aim to provide objective guidance and critical considerations. They offer insights into implementing environmentally sound treatment and disposal solutions. The guides include: (i) A basic description of what each technology is and how it works; (ii) Key considerations when thinking about pursuing a specific technology; (iii) Financial implications and suggestions for reducing and recovering costs; (iv) Examples of where the technology has succeeded and failed; and (v) Questions to ask the solid waste vendor to assess appropriateness of the technology and vendor for the local context.